Awaking Blood Pressure Surge and Progression to Microalbuminuria in Type 2 Normotensive Diabetic Patients - Michelangela Barbieri; Maria Rosaria Rizzo; Ilaria Fava; Celestino Sardu; Nicola Angelico; Pasquale Paolisso; Angela Abbatecola; Giuseppe Paolisso; Raffaele Marfella (Journal of Diabetes Research)
Background. We investigated the predictive value of morning blood pressure surge (MBPS) on the development of microalbuminuria in normotensive adults with a recent diagnosis of type 2 diabetes. Methods. Prospective assessments of 24-hour ambulatory blood pressure monitoring and urinary albumin excretion were performed in 377 adult patients. Multivariate-adjusted Cox regression models were used to assess hazard ratios (HRs) between baseline and changes over follow-up in MBPS and the risk of microalbuminuria. The MBPS was calculated as follows: mean systolic BP during the 2 hours after awakening minus mean systolic BP during the 1 hour that included the lowest sleep BP. Results. After a mean follow-up of 6.5 years, microalbuminuria developed in 102 patients. An increase in MBPB during follow-up was associated with an increased risk of microalbuminuria. Compared to individuals in the lowest tertile (−0.67±1.10 mmHg), the HR and 95% CI for microalbuminuria in those in the highest tertile of change (24.86±6.92 mmHg) during follow-up were 17.41 (95% CI 6.26–48.42); p for trend <0.001. Mean SD MBPS significantly increased in those who developed microalbuminuria from a mean [SD] of 10.6 [1.4] to 36.8 [7.1], p<0.001. Conclusion. An increase in MBPS is associated with the risk of microalbuminuria in normotensive adult patients with type 2 diabetes.